PERSEPSI KONSUMEN TERHADAP SATE DAGING KAMBING DI KECAMATAN SANGATA UTARA KABUPATEN KUTAI TIMUR - Ida Indrawati Waang; Nursida Nursida; Joni Ariansyah (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2019)
This study aims to determine consumer perceptions of goat sate in North Sangatta base on personal aspects, social aspects, religious and cultural aspects, psychology aspects and product aspects. This studu have been done on Maret until April, 2018 in several food stalls that sell goat sate in the north Sangata sub-district. The sampling technique used is incidental sampling with total respondents is 30 buyers. Data is analyzed descriptively with a scoring method using a Likert scale. This study result had show that personal apsects is cunsumers agree if they buy goat sate accordance with their practical lifestyle and favorite food with perception value is 7.13. Perception value from social aspects is 10.43 which means that consumers agree if they buy goat sate because of recommendations by friend and family believes that the taste and quality of goat sate is good. Religious and cultural aspects, perception value is 7.60 means that consumers disagree if consume goat sate contrary to religion and relieve trust. Psychology aspects with value is 14.30 result that consumers agree if goat sate is bad smell, can increase blood pressure and body vitality, and cook it long time. Product aspects, consumers also agree that the price of goat sate is more expensive than other sate, sale location are hard to find, less promotion, tastyseasoning, tough, less attractive presentation, aesthetics of a place to sell poorly with perception value is 25.60.